Impact of the Charlson Comorbidity Index on dose-limiting toxicity and survival in locally advanced and metastatic renal cell carcinoma patients treated with first-line sunitinib or pazopanib - ÇİÇEK, FURKAN CUMA; ALSAN ÇETİN, İLKNUR; DEMİRCAN, NAZIM CAN; YUMUK, PERRAN FULDEN; ERGELEN, RABİA; ARIKAN, RUKİYE (SAGE PUBLICATIONS LTD, 2020)
Background Anti-angiogenic tyrosine kinase inhibitors, sunitinib and pazopanib, have proven efficacy in advanced renal cell carcinoma, with specific adverse events occurring during treatment process. Comorbidities can reflect functional status and have prognostic value in oncology patients. We aimed to assess the association of the Charlson Comorbidity Index with severe toxicities and mortality in renal cell carcinoma cases treated with front-line sunitinib or pazopanib. Methods Files of locally advanced and metastatic renal cell carcinoma patients who received first-line sunitinib or pazopanib were retrospectively examined. Charlson Comorbidity Index of each patient was calculated. Patients were also stratified into Memorial Sloan-Kettering Cancer Center risk groups. Predictors of dose-limiting toxicity were evaluated with binomial logistic regression analysis. Univariate and multivariate Cox regression models were utilized to determine prognostic factors for survival. Results The study included 102 patients, 64 were treated with first-line sunitinib and 38 with pazopanib. In 42 patients (41.9%), Charlson Comorbidity Index was 9 or more. Dose-limiting toxicities were significantly more frequent in Charlson Comorbidity Index >= 9 group (69% vs. 40%, p = 0.004), and Charlson Comorbidity Index independently predicted dose-limiting toxicity (Hazard ratio (HR) = 4.30, p = 0.002). After adjusting for other variables, a Charlson Comorbidity Index of >= 9 is also a significant prognostic factor for progression-free (HR = 1.76, p = 0.02) and overall survival (HR = 1.75, p = 0.03). Conclusions Charlson Comorbidity Index may be a valuable method to estimate prognosis and optimize therapy in patients with advanced renal cell carcinoma receiving first-line sunitinib or pazopanib.
Keywords: Charlson Comorbidity Index; dose-limiting toxicity; prognostic factor; renal cell carcinoma; tyrosine kinase inhibitor; INTERFERON-ALPHA; DOUBLE-BLIND; PHASE-III; CANCER; NEPHRECTOMY